TRANSFORMASI DIGITAL DALAM PEMBELAJARAN ANAK USIA DINI: PELUANG DAN TANTANGAN - Asnah Asnah; Kadim Bustami (lembaga Sepercenter, 2025)
The swift growth of digital technology has reshaped how young children learn, pushing educators to rethink pedagogical strategies so they still match children's developmental stages. This article sets out to systematically map the use of digital technology in early childhood education and how it reshapes the learning process. A Systematic Literature Review (SLR) approach was applied, in which relevant articles from national journals were located, screened, and analyzed through defined stages — formulating research questions, setting inclusion and exclusion criteria, and synthesizing the findings. The review shows that digital technology works best as a supporting tool: it lifts children's engagement, enriches learning through play-based and interactive activities, and contributes to cognitive, language, social-emotional, and creative growth. Even so, how well this integration works hinges on teachers' competence, sound instructional design, measured use of devices, and parents staying involved in guiding children's digital activity. The study concludes that digital technology can genuinely transform early childhood learning for the better, provided it is applied thoughtfully, systematically, and in step with developmental principles. These insights are intended to help educators and researchers design early childhood learning that is both innovative and meaningful in the digital era.